Selectivity and sub-lethal effect of pesticides on the immature and adult stages of Telenomus podisi (Hymenoptera: Scelionidae) - Santos, Leonardo Vieira [UNESP]; de Lima Alvarez, Daniel [UNESP]; Santos, Lucas Moraes [UNESP]; do Prado, Jean Carlo [UNESP]; de Freitas Bueno, Regiane Cristina Oliveira [UNESP]; Hoback, William Wyatt (Springer Nature, 2022)
Determining the effects of pesticides on all life stages of natural enemies is essential within Integrated Pest Management (IPM) programas, as an aid to minimize non-target effects and preserve beneficial insects. This study evaluated the selectivity and effects of pesticide residues on adults of the egg parasitoid wasp Telenomus podisi and its immatures when host eggs were treated. Fungicides, insecticides, and adjuvants were tested at field rates along with distilled water as a control. Based on parasitoid mortality and rate of parasitism, the products were assigned to four classes: 1, harmless (<30%); 2, slightly harmful (30-79%); 3, moderately harmful (80-99%) and 4, harmful (> 99%). For adult T. podisi exposed to pesticide residues, all treatments were harmless when evaluating parasitism rate except thiamethoxan + lambda-cyhalothrin (Class 3). Pyriproxyfen (Class 2) and thiamethoxan + lambda-cyhalothrin (Class 3) were harmful to the viability of T. podisi that emerged from parasitized eggs, while the other treatments were harmless. Azoxystrobin (Class 1), fluxapyroxad + pyraclostrobin (Class 1), pyriproxyfen (Class 1) and water (Class 1) were innocuous to the viability of T. podisi larvae in parasitized eggs that were exposed to pesticides. Treatment exposure reduced adult female longevity from a maximum of 23 days (teflubenzuron) to a minimum of 1 day (chlorpyrifos). The lifespan of the females treated while in host eggs ranged from 7 days (pyriproxyfen) to 14 days (water). Overall, the pesticides tested pose the most risk to emerged adult T. podisi and pose less threat when parasitoids are protected inside host eggs.
Keywords: Chemical control; Egg parasitoids; Non-target effects; Parasitoids